2009
DOI: 10.4028/www.scientific.net/amr.67.173
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion Behaviour of Amorphous and Nanocrystalline Ti<sub>60</sub>Ni<sub>40</sub> in Aqueous HNO<sub>3</sub> Solution

Abstract: Potentiodynamic polarization studies were carried out on amorphous, nanocrystalline and crystalline states of the alloy Ti60Ni40 in 0.1 M HNO3, 0.5 M HNO3 and 1 M HNO3 aqueous solutions at room temperature. It was observed that the amorphous state exhibited higher corrosion current density than that by the nanocrystalline state. These results are corroborated by the weight loss studies performed on the different structural states of Ti60Ni40 alloy in 0.1 M HNO3, 0.5 M HNO3 and 1 M HNO3 aqueous media. Thus the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2010
2010
2012
2012

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 7 publications
(19 citation statements)
references
References 22 publications
1
18
0
Order By: Relevance
“…It was observed that nanocrystalline phase (Ti 2 Ni) appeared after irradiation of the amorphous specimen with a crystallite size of about 4-5 nm. The crystallite size of 10-12 nm was found in the case of nanocrystalline specimen [14]. The crystallite size was obtained by using the Debye Scherrer formula [18].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…It was observed that nanocrystalline phase (Ti 2 Ni) appeared after irradiation of the amorphous specimen with a crystallite size of about 4-5 nm. The crystallite size of 10-12 nm was found in the case of nanocrystalline specimen [14]. The crystallite size was obtained by using the Debye Scherrer formula [18].…”
Section: Resultsmentioning
confidence: 99%
“…The details about the experimental procedure and calculation of the corrosion current density can be found in another paper [17]. The electrochemical behavior of the virgin specimen of the nanocrystalline form of the same alloy in 1 M HNO3 has earlier been reported in another investigation [14].…”
Section: Methodsmentioning
confidence: 97%
See 3 more Smart Citations